Prevalence of non‐alcoholic fatty liver disease and factors associated with it in Indian women with a history of gestational diabetes mellitus. Issue 5 (26th October 2020) - Kubihal, Suraj; Gupta, Yashdeep; Shalimar,; Kandasamy, Devasenathipathy; Goyal, Alpesh; Kalaivani, Mani; Goyal, Ankur; Kedia, Saurabh; Kachhawa, Garima; Ambekar, Samita; Bhatia, Divya; Garg, Vineeta; et al.
Abstract: Aims/Introduction: This study aims to evaluate the prevalence of and factors associated with non‐alcoholic fatty liver disease (NAFLD) in Indian women with prior gestational diabetes mellitus (GDM) diagnosed using International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria. Materials and Methods: This cross‐sectional study (2018–2019) enrolled women with and without prior GDM. Study participants underwent detailed assessments, including relevant medical, obstetric and demographic details; 75‐g oral glucose tolerance test with glucose and insulin estimation at 0, 30 and 120 min; and other relevant biochemical and anthropometric measurements. NAFLD status was defined by ultrasonography. Results: We evaluated a total of 309 women (201 and 108 with and without prior GDM, respectively) at a mean age of 31.9 ± 5.0 years and median of 16 months (interquartile range 9–38 months) following the index delivery. The prevalence of NAFLD was significantly higher in women with prior GDM (62.7% vs 50.0%, P  = 0.038; grade 2 and 3 disease, 13.9% vs 6.5%). On logistic regression analysis (fully adjusted model), the odds of NAFLD were 2.11‐fold higher in women with prior GDM (95% confidence interval 1.16–3.85, P  = 0.014). Overweight/obesity, metabolic syndrome, prediabetes and homeostasis model of assessment of insulin resistance (a measure of insulin resistance) were positively associated with NAFLD, whereas the Matsuda index (a measure of insulin sensitivity) showed a negative association with NAFLD. Conclusions: The prevalence of NAFLD is high in women with prior GDM. Such women also have a high burden of cardiometabolic risk factors. Future studies should evaluate the intermediate and long‐term hepatic and cardiovascular risk, and the impact of lifestyle interventions in reducing morbidity in such women. Abstract : This study evaluated the prevalence and risk factors of non‐alcoholic fatty liver disease in Indian women with prior gestational diabetes mellitus diagnosed using International Association of Diabetes and Pregnancy Study Groups criteria. Ultrasonography of abdomen was used to define non‐alcoholic fatty liver disease status. Prevalence of non‐alcoholic fatty liver disease was significantly higher in women with prior gestational diabetes mellitus (62.7% vs 50.0%, P  = 0.038; grade 2 and 3 disease, 13.9% vs 6.5%).